Patients’ perception and needs of spiritual care: A qualitative study in the context of prolonged hospitalizations - Rahime Aydin Er; Gamze Çetiner; Yüksel Can Öz (PLoS ONE, 2026)
Spiritual care is recognized as a core component of holistic nursing, particularly for patients experiencing prolonged hospitalization. Extended hospital stays may intensify spiritual needs by disrupting daily routines, limiting engagement in religious practices, and increasing existential distress. However, empirical evidence on patients’ spiritual care needs and their perceptions of nursing practices remains limited. This study aimed to explore patients’ spiritual care needs during prolonged hospitalization and to examine their perceptions of spiritual care provided by nurses. A qualitative study with a descriptive phenomenological design was conducted. Semi-structured, in-depth interviews were carried out with 12 patients hospitalized in internal medicine clinics for more than 14 days. Data were analysed using an inductive thematic analysis approach. Participants described spirituality as encompassing both religious practices and broader dimensions such as inner peace, psychological balance, and meaning making. Spiritual needs were frequently reflected in participants’ use of religious rituals, including prayer, ablution, and supplication, reflecting a desire for closeness to God. In addition, nurse–patient communication, empathetic attitudes, psychosocial support, and assistance with personal hygiene were identified as integral components of spiritual care. Environmental and institutional factors, including shared rooms, limited access to prayer spaces, and inadequate hygiene conditions, emerged as significant barriers to meeting spiritual needs. The findings demonstrate that spiritual care in prolonged hospitalization is a multidimensional process encompassing relational, physical, and environmental dimensions of care. Addressing spiritual needs requires both compassionate communication and supportive clinical environments that enable patients to sustain their spiritual practices. Integrating spiritual care into routine nursing practice may enhance patient experience and strengthen the holistic nature of care.